Strategies of subversion in vertically-divided contexts: Decentralisation and urban service delivery in Senegal - Resnick, Danielle (Wiley, 2014)
Focusing on the case of Senegal under the former President, Abdoulaye Wade, this article examines the impact party politics has on service delivery in urban areas controlled by opposition parties. Senegal's decentralisation process provided opportunities for the central government to deliberately reduce the autonomy of local government under conditions in which the latter could be held accountable for good service delivery and increase autonomy when local government could be targeted for poor performance – actions manifested through backtracking on political decentralisation, undermining fiscal decentralisation, and augmenting administrative ambiguity. The case offers useful implications for donors involved in decentralisation and urban service‐delivery projects in opposition‐controlled cities.